Management of parapneumonic effusions and empyema. - Psallidas, I; Corcoran, J; Rahman, N (Thieme Medical Publishers, Inc., 2014)
Pleural infection remains a common and serious respiratory condition with important implications for patients and health-care services. This review will cover the management of pleural infection including medical treatment, the role of intrapleural agents and surgical treatment. We discuss the directions that future research in this important area might take. Increasing incidence of pleural infection has been reported worldwide without a clear explanation. The pathogens responsible for pleural infection differ from those in pneumonia. Proper antibiotic selection and pleural fluid drainage remain the cornerstones of treatment. There is no evidence in adult pleural infection to support the routine use of intrapleural fibrinolytics to alter clinically meaningful outcomes; however, combined intrapleural tissue plasminogen activator (tPA) and deoxyribonuclease (DNase) therapy may have a future role. The role of medical thoracoscopy remains unproven. Surgical referral should be considered in patients who fail to respond to standard medical management after 5 to 7 days. Despite advances in microbiology, medical management, and surgery, the mortality of pleural infection at one year remains approximately 20% for the last two decades. Future studies are required to validate predictive scores for patients' stratification (RAPID score) and the role of fibrinolytics (combination of tPA plus DNase). Surgical drainage remains a vital treatment option, but ongoing research is required to define the group of patients who would benefit most and when, in the disease course, this treatment should be offered.